Respuesta :

DeanR

For the usual equation

[tex]\dfrac{x^2}{a^2} + \dfrac{y^2}{b^2}=1[/tex]

the distance c from one of the foci to the center is given by

[tex]c^2 = a^2 - b^2[/tex]

The major axis is actually 2a, the minor axis 2b, and the distance between the two foci is 2c, so the same formula with the doubled numbers gives the distance we seek,

[tex]\sqrt{68^2 - 60^2} = \sqrt{(4(17))^2 - (4(15))^2} =4\sqrt{17^2-15^2}=4(8)=32[/tex]

Answer: 32

Answer:

the answer is 32

~batmans wife dun dun dun

ACCESS MORE